Nano silver powder for low-temperature sintering type water-based polyester-based conductive paste and preparation method of nano silver powder

The nano silver powder is prepared by reaction in the compound dispersant solution, and the problems of poor dispersion and easy collapse of nano silver powder in the low-temperature sintered polyester-based conductive paste are solved, and the nano silver powder is prepared efficiently and suitable for water properties is achieved. Polyester-based conductive paste improves conductive performance and production efficiency.

CN119304201APending Publication Date: 2025-01-14CSSC HUANGGANG PRECIOUS METALS CO LTD +1

Patent Information

Application Number
CN202411362582.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The dispersion of nano silver powder in existing low-temperature sintered polyester-based conductive paste is poor, difficult to wash, and easy to collapse after sintering, which affects its application performance.

Method used

The nano-silver powder is prepared by reacting silver nitrate, reducing agent and flocculant in a compound dispersant solution. The nano-silver powder is well dispersed by stirring and solid-liquid separation, and then dried and crushed, with a controlled mass ratio of (1000-1500): ( 500-1000): (20-60) to achieve efficient preparation of nano-silver powder for low-temperature sintered aqueous polyester-based conductive paste.

Benefits of technology

The prepared nano silver powder has high dispersion, easy to wash, small particle size, high density, and does not collapse easily after sintering. It is suitable for low-temperature sintered water-based polyester-based conductive paste, improving conductive performance and production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119304201A_ABST
    Figure CN119304201A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps that S1, a silver nitrate solution and a reducing agent solution are added into a compound dispersing agent solution at the same time, stirring reaction is conducted, and a nanometer silver powder suspension is obtained; s2, adding a flocculant solution into the nano silver powder suspension, and stirring for reaction to obtain a reaction solution; and S3, carrying out solid-liquid separation on the reaction liquid to obtain a solid component, and then drying and crushing to obtain the nano silver powder for the low-temperature sintering type water-based polyester-based conductive paste. The mass ratio of the silver nitrate to the reducing agent to the compound dispersing agent to the flocculating agent is (1000-1500): (500-1000): (20-60): (3-8); according to the preparation method, the mixed dispersing agent, the silver nitrate solution, the reducing agent solution and the flocculating agent react to obtain the nano silver powder which is good in dispersity, high in yield, smooth in surface, small in particle size and high in apparent density and tap density, and preparation of the low-temperature sintering type waterborne polyester-based conductive paste is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive materials, and in particular to a nano silver powder for low-temperature sintering water-based polyester-based conductive paste and a preparation method thereof. Background Art

[0002] In recent years, the electronic information manufacturing industry, such as integrated circuits, new display technologies, and the Internet of Things, has entered a rapid development stage and has gradually become intelligent, information-based, and lightweight. Therefore, it is urgent to develop new materials and technologies to replace traditional tin-lead solder and copper foil circuit printing technologies. Conductive paste is a key material in the fields of nano-conductive inks, printed circuits, printed electronic devices, etc. According to different curing processes, conductive pastes can be divided into high-temperature sintering types with glass powder added to the adhesive, low-temperature sintering types using polyester-based adhesives, and UV curing types irradiated by ultraviolet rays. Since polymers have the lowest density and are easy to process, conductive pastes formed by mixing polymers and conductive particles have the characteristics of light weight and good conductivity. In addition, low-temperature sintering pastes have low curing temperatures and fast speeds, and have excellent room-temperature conductivity, hardness, and adhesion. They are often used to make membrane switches and printed circuit boards, and are widely used in the flexible electronics industry, electronic packaging, and heterojunction solar cells. Traditional low-temperature sintering polyester-based conductive pastes usually choose oil-soluble polyesters as the bonding phase, which are prone to produce volatile organic compounds during the curing process, causing air pollution. Therefore, using water-based polyester as the bonding phase can reduce environmental pollution and is in line with the current trend of sustainable development and the concept of green environmental protection.

[0003] In addition to the bonding phase, the conductive paste is also composed of a functional phase, solvents and additives. Among them, the functional phase determines the electrical properties of the conductive paste. Nano silver powder particles are considered to be the best functional phase for conductive pastes because of their low resistivity, stable physical and chemical properties, and excellent optical and electrical properties. At present, the preparation of nano silver powder for low-temperature sintering polyester-based conductive pastes is mainly based on monodispersants, and the amount must reach 50% of the mass of silver nitrate to prepare nano silver powder with a smooth surface and good dispersion. It is also difficult to wash clean in the subsequent process, and the prepared downstream paste end is also prone to collapse after sintering.

[0004] Therefore, it is necessary to provide a nano silver powder with good dispersibility, easy washing, and not easy to collapse after slurry sintering so as to be suitable for low-temperature sintering water-based polyester-based conductive slurry. Summary of the invention

[0005] In view of this, the present application provides a nano silver powder for low-temperature sintering water-based polyester-based conductive paste and a preparation method thereof, which is used to solve the problem of how to achieve good dispersibility of nano silver powder, easy washing, and non-settling of the paste after sintering.

[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste, comprising the following steps: S1. The silver nitrate solution and the reducing agent solution are simultaneously added to the compound dispersant solution, and the reaction is stirred to obtain a nanosilver powder suspension; S2. Add a flocculant solution to the nanosilver powder suspension, stir the reaction, and obtain a reaction solution; S3. The reaction solution was subjected to solid-liquid separation to obtain a solid component, which was then dried and crushed to obtain a low-temperature sintered water-based polyester-based conductive paste with nano silver powder; The mass ratio of silver nitrate, reducing agent, compound dispersant and flocculant is (1000-1500): (500-1000): (20-60): (3-8).

[0007] Preferably, the composite dispersant includes two or more of succinic acid, polyacrylic acid, gum arabic, guar gum, polyvinyl pyrrolidone, polyethylene glycol, gelatin, Tween, citric acid, polyvinyl alcohol, nonylphenol polyoxyethylene ether, sodium lauryl sulfate, Triton X-100, triethanolamine, and benzotriazole.

[0008] Preferably, the reducing agent includes one or more of formaldehyde, glucose, ascorbic acid, hydrazine hydrate and glycerol.

[0009] Preferably, the flocculant includes one or more of ricinoleic acid, stearic acid, lauric acid, and arachidic acid.

[0010] Preferably, the pH value of the compound dispersant solution is 9-12.

[0011] Preferably, the concentration of the silver nitrate solution is 0.2-0.8 kg / L, the concentration of the reducing agent solution is 0.1-0.5 kg / L, and the concentration of the flocculant solution is 0.05-0.08 kg / L.

[0012] Preferably, the mass of the compound dispersant is 2-8% of the total mass of the silver nitrate solution, the reducing agent solution and the compound dispersant solution.

[0013] Preferably, the specific operation of step S3 is: the reaction solution is allowed to stand for 24-36 hours to settle, and black nano silver powder precipitates appear at the bottom of the reactor to obtain a solid component, and then the solid component is filtered with a filter paper with a mesh number of ≥600 and washed to a conductivity of ≤30 μS / cm, and then dried at 50-80°C, the dried silver powder is crushed with an air mill, and then sieved with 60 mesh to obtain nano silver powder for low-temperature sintering water-based polyester-based conductive paste.

[0014] In a second aspect, the present application provides a nano silver powder.

[0015] In a third aspect, the present application provides a conductive paste comprising a water-based polyester-based resin and nano silver powder.

[0016] The beneficial effects of the present application are as follows: the present application mainly uses a mixed dispersant, and adopts a silver nitrate solution, a reducing agent solution and a flocculant to react to prepare a nano silver powder with good dispersibility, high yield, smooth surface, small particle size, high bulk density and high tap density. The nano silver powder has a nano size of 200-400 nm, a bulk density of ≥1.95 g / mL, a tap density of ≥4.02 g / mL, and a specific surface area of ​​≥1.56 m 2 / g, Malvern laser particle size analyzer tested particle size distribution D50≤0.34 µm, D90≤0.84 µm, D100≤2.7 µm, single batch 1 kg-5 kg ​​silver powder yield is ≥99.2%, which can achieve the effects of good dispersibility, easy washing, and non-easy collapse of the slurry after sintering, which is conducive to the preparation of low-temperature sintering water-based polyester-based conductive slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the silver powder prepared in Example 1 at a magnification of 15.0 k; Figure 2 This is a scanning electron microscope image of the silver powder prepared in Example 1 at a magnification of 10.0 k. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0019] The present application provides a method for preparing nano silver powder for low temperature sintering water-based polyester-based conductive paste, comprising the following steps: S1. The silver nitrate solution and the reducing agent solution are simultaneously added to the compound dispersant solution, and the reaction is stirred to obtain a nanosilver powder suspension; S2. Add a flocculant solution to the nanosilver powder suspension, stir the reaction, and obtain a reaction solution; S3. The reaction solution was subjected to solid-liquid separation to obtain a solid component, which was then dried and crushed to obtain a low-temperature sintered water-based polyester-based conductive paste with nano silver powder; The mass ratio of silver nitrate, reducing agent, compound dispersant and flocculant is (1000-1500): (500-1000): (20-60): (3-8).

[0020] The specific operation in step S1 is as follows: silver nitrate, a reducing agent, and a compound dispersant are dissolved in deionized water, respectively, to obtain a silver nitrate solution, a reducing agent solution, and a compound dispersant solution, the stirring rate of the reducing agent dissolved in deionized water is 200-500 rpm, the stirring rate of the dispersant dissolved in deionized water is 300-600 rpm, and the pH condition of the compound dispersant solution is adjusted by an alkali solution, wherein the alkali solution includes but is not limited to one or more of sodium hydroxide, ammonia water, and sodium carbonate; at a stirring rate of 300-600 rpm, the silver nitrate solution and the reducing agent solution are added in a counter-addition manner to the compound dispersant solution with the pH adjusted, to obtain a nano silver powder suspension, and the addition rate of the silver nitrate solution and the reducing agent solution is 40-45 mL / s.

[0021] In step S2, the stirring rate of the stirring reaction is 400-800 rpm, and the reaction time is 20-60 min.

[0022] In some embodiments, the composite dispersant includes two or more of succinic acid, polyacrylic acid, gum arabic, guar gum, polyvinyl pyrrolidone, polyethylene glycol, gelatin, Tween, citric acid, polyvinyl alcohol, nonylphenol polyoxyethylene ether, sodium lauryl sulfate, Triton X-100, triethanolamine, and benzotriazole. The components of the composite dispersant are selected to be of the same category, for example, all organic acids, all colloids, all polymers, or all surfactants, and the composite ratio between the components is not limited.

[0023] In some embodiments, the reducing agent includes one or more of formaldehyde, glucose, ascorbic acid, hydrazine hydrate, and glycerol.

[0024] In some embodiments, the flocculant includes one or more of ricinoleic acid, stearic acid, lauric acid, and arachidic acid.

[0025] In some embodiments, the pH value of the compounded dispersant solution is 9-12.

[0026] In some embodiments, the concentration of the silver nitrate solution is 0.2-0.8 kg / L, the concentration of the reducing agent solution is 0.1-0.5 kg / L, the concentration of the flocculant solution is 0.05-0.08 kg / L, and the flocculant solution is a solution obtained by dissolving the flocculant in ethanol.

[0027] In some embodiments, the mass of the compound dispersant is 2-8% of the total mass of the silver nitrate solution, the reducing agent solution and the compound dispersant solution.

[0028] In some embodiments, the specific operation of step S3 is: the reaction solution is allowed to stand for 24-36 hours to settle, and the obtained solid component is filtered with filter paper with a mesh size of ≥600 and washed to a conductivity of ≤30 μS / cm, and then dried at 50-80°C, and then crushed and sieved with 60 mesh to obtain nano silver powder for low-temperature sintering water-based polyester-based conductive paste.

[0029] The present application provides a nano silver powder, wherein the nano size of the nano silver powder is between 200-400 nm, the bulk density of the nano silver powder is ≥1.95 g / mL, the tap density is ≥4.02 g / mL, and the specific surface area is ≥1.56 m 2 / g, Malvern laser particle size analyzer test particle size distribution D50≤0.34 µm, D90≤0.84 µm, D100≤2.7 µm, single batch 1 kg-5 kg ​​silver powder yield is ≥99.2%. The surface of nano silver powder is smooth and easy to wash, the particle size is small and the loose density and tap density are high, which can achieve the effect of not easy collapse after sintering the slurry, and at the same time, the dispersibility is good.

[0030] The present application provides a conductive paste, which includes a water-based polyester-based resin and nano silver powder.

[0031] The cross-linked network water-based polyester-based resin has strong polarity and good compatibility with the nano silver powder of the present application, which is more conducive to the dispersion of the nano silver powder. The prepared conductive silver paste has high hardness and better bonding with the substrate.

[0032] The present solution is further described below through specific embodiments.

[0033] Example 1 A method for preparing nano silver powder for low temperature sintering water-based polyester-based conductive paste comprises the following steps: S1. Weigh 1.6 kg of silver nitrate and dissolve it in 6 L of deionized water to obtain a silver nitrate solution, weigh 860 g of ascorbic acid and dissolve it in 6 L of deionized water to obtain a reducing agent solution, weigh 4.4 g of ricinoleic acid and dissolve it in 80 mL of anhydrous ethanol to obtain a flocculant solution, weigh 4% of the total mass of the silver nitrate solution, the reducing agent solution and the composite dispersant solution, and 1.25% of gelatin to compound, and then add water to dissolve to obtain a composite dispersant solution; add sodium carbonate to the composite dispersant solution to adjust the pH to 10 as a primer, stir continuously at a rate of 400 rpm for 15 min, add the silver nitrate solution and the ascorbic acid solution to the primer at a rate of 42 mL / s, and after the addition is completed, obtain a nano silver powder suspension; S2. Immediately add the flocculant solution to the nanosilver powder suspension and stir the reaction, wherein the stirring rate is 500 rpm and the reaction time is 30 min to obtain a reaction solution; S3. The reaction solution was allowed to stand for 24 h, and filtered using a Buchner funnel with a filter paper mesh of ≥600 mesh. The solution was washed until the conductivity was ≤30 μS / cm. The solid component was dried in a 70°C air drying oven for 24 h, crushed using an air mill, and sieved through 60 mesh to obtain nano silver powder for low-temperature sintering water-based polyester-based conductive paste.

[0034] Example 2 A method for preparing nano silver powder for low temperature sintering water-based polyester-based conductive paste comprises the following steps: S1. Weigh 1.6 kg of silver nitrate and dissolve it in 6 L of deionized water to obtain a silver nitrate solution, weigh 860 g of ascorbic acid and dissolve it in 6 L of deionized water to obtain a reducing agent solution, weigh 4.4 g of lauric acid and dissolve it in 80 mL of anhydrous ethanol to obtain a flocculant solution, weigh 5% of polyvinyl pyrrolidone and 0.28% of nonylphenol polyoxyethylene ether, which account for the total mass of the silver nitrate solution, the reducing agent solution and the composite dispersant solution, and then add water to dissolve to obtain a composite dispersant solution; add sodium carbonate to the composite dispersant solution to adjust the pH to 10.8 as a primer, stir continuously at a rate of 450 rpm for 10 min, add the silver nitrate solution and the ascorbic acid solution to the primer at a rate of 40 mL / s, and after the addition is completed, obtain a nano silver powder suspension; S2. Immediately add the flocculant solution to the nanosilver powder suspension and stir the reaction, wherein the stirring rate is 550 rpm, the reaction time is 25 min, and the reaction solution is obtained; S3. The reaction solution was allowed to stand for 24 h, and filtered using a Buchner funnel with a filter paper mesh of ≥600 mesh. The solution was washed until the conductivity was ≤30 μS / cm. The solid component was dried in a 60°C air drying oven for 24 h, crushed using an air mill, and sieved through 60 mesh to obtain nano silver powder for low-temperature sintering water-based polyester-based conductive paste.

[0035] Example 3 A method for preparing nano silver powder for low temperature sintering water-based polyester-based conductive paste comprises the following steps: S1. Weigh 1.6 kg of silver nitrate and dissolve it in 6 L of deionized water to obtain a silver nitrate solution, weigh 860 g of ascorbic acid and dissolve it in 6 L of deionized water to obtain a reducing agent solution, weigh 4.4 g of stearic acid and dissolve it in 80 mL of anhydrous ethanol to obtain a flocculant solution, weigh 3% of citric acid and 2.5% of succinic acid, which account for the total mass of the silver nitrate solution, the reducing agent solution and the composite dispersant solution, and then add water to dissolve to obtain a composite dispersant solution; add sodium carbonate to the composite dispersant solution to adjust the pH to 11 as a primer, stir continuously at a rate of 350 rpm for 15 min, add the silver nitrate solution and the ascorbic acid solution to the primer at a rate of 40 mL / s, and after the addition is completed, obtain a nano silver powder suspension; S2. Immediately add the flocculant solution to the nanosilver powder suspension and stir the reaction, wherein the stirring rate is 450 rpm, the reaction time is 40 min, and the reaction solution is obtained; S3. The reaction solution was allowed to stand for 24 h, and filtered using a Buchner funnel with a filter paper mesh of ≥600 mesh. The solution was washed until the conductivity was ≤30 μS / cm. The solid component was dried in an air drying oven at 80°C for 24 h, crushed using an air mill, and sieved through 60 mesh to obtain nano silver powder for low-temperature sintering water-based polyester-based conductive paste.

[0036] Comparative Example 1 A method for preparing nano silver powder for low-temperature sintering water-based polyester-based conductive paste, the other contents are the same as those of Example 1, except that 40% of gum arabic and 12.5% ​​of gelatin, which account for the total mass of the silver nitrate solution, the reducing agent solution and the compound dispersant solution, are weighed and compounded, and then water is added to dissolve to obtain the compound dispersant solution.

[0037] Comparative Example 2 A method for preparing nano silver powder for low-temperature sintering water-based polyester-based conductive paste, the other contents are the same as those of Example 1, except that gelatin is replaced by gum arabic.

[0038] Test and Evaluation The bulk density, tap density, specific surface area, D50, D90, D100 and silver powder yield of the nano silver powders obtained in different embodiments and comparative examples were tested, and the results are shown in Table 1.

[0039] Table 1 Test results

[0040] As shown in Table 1, the present invention mainly uses a mixed dispersant, and adopts a silver nitrate solution, a reducing agent solution and a flocculant to react to prepare a nano silver powder with good dispersibility, high yield, smooth surface, small particle size, high bulk density and high tap density. The nano silver powder prepared by the tap density meter is observed under an electron microscope. The nano size is between 200-400 nm, and the bulk density of the nano silver powder is ≥1.95 g / mL, the tap density is ≥4.02 g / mL, and the specific surface area is ≥1.56 m 2 / g, Malvern laser particle size analyzer tested particle size distribution D50≤0.34 µm, D90≤0.84 µm, D100≤2.7 µm, single batch 1 kg-5 kg ​​silver powder yield ≥99.2%; while the silver powder sample prepared in comparative example 1 maintained a particle size of 0.28-3.39 μm, and the silver powder sample prepared in comparative example 2 maintained a particle size of 0.29-3.49 μm, with a wide particle size distribution, which is not conducive to subsequent winding, and the tap density is small. The nano silver powder of the present application can achieve the effects of good dispersibility, easy washing, and not easy to collapse after slurry sintering, which is conducive to the preparation of low-temperature sintering water-based polyester-based conductive slurry.

[0041] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste, characterized in that: The following steps are involved: S1. The silver nitrate solution and the reducing agent solution are simultaneously added to the compound dispersant solution, and the reaction is stirred to obtain a nanosilver powder suspension; S2. Adding a flocculant solution to the nanosilver powder suspension, stirring the reaction to obtain a reaction solution; S3. The reaction solution is subjected to solid-liquid separation to obtain a solid component, which is then dried and crushed to obtain the low-temperature sintering waterborne polyester-based conductive paste with nano silver powder; The mass ratio of the silver nitrate, the reducing agent, the compound dispersant and the flocculant is (1000-1500): (500-1000): (20-60): (3-8).

2. The method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste according to claim 1, characterized in that: The compound dispersant comprises two or more of succinic acid, polyacrylic acid, gum arabic, guar gum, polyvinyl pyrrolidone, polyethylene glycol, gelatin, Tween, citric acid, polyvinyl alcohol, nonylphenol polyoxyethylene ether, sodium lauryl sulfate, Triton X-100, triethanolamine and benzotriazole.

3. The method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste according to claim 1, characterized in that: The reducing agent includes one or more of formaldehyde, glucose, ascorbic acid, hydrazine hydrate and glycerol.

4. The method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste according to claim 1, characterized in that: The flocculant includes one or more of ricinoleic acid, stearic acid, lauric acid and arachidic acid.

5. The method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste according to claim 1, characterized in that: The pH value of the compound dispersant solution is 9-12.

6. The method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste according to claim 1, characterized in that: The concentration of the silver nitrate solution is 0.2-0.8 kg / L, the concentration of the reducing agent solution is 0.1-0.5 kg / L, and the concentration of the flocculant solution is 0.05-0.08 kg / L.

7. The method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste according to claim 1, characterized in that: The mass of the compound dispersant is 2-8% of the total mass of the silver nitrate solution, the reducing agent solution and the compound dispersant solution.

8. The method for preparing nano silver powder for low temperature sintering waterborne polyester-based conductive paste according to claim 1, characterized in that: The specific operation of step S3 is: the reaction solution is allowed to stand for 24-36 hours to settle, and the obtained solid component is filtered with filter paper with a mesh size of ≥600 and washed to a conductivity of ≤30 μS / cm, and then dried at 50-80° C., and then crushed and sieved with 60 mesh to obtain the nano silver powder for the low-temperature sintering water-based polyester-based conductive paste.

9. A nano silver powder obtained by the preparation method according to any one of claims 1 to 8.

10. A conductive paste, characterized in that: The invention comprises a water-based polyester-based resin and the nano silver powder as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of high-tap-density small-granularity sphere-like silver powder for LTCC (low temperature co-fired ceramic) inner electrode

    CN114713838A

  • Geothermal film conductive silver paste and preparation method thereof

    CN115312229A

  • Silver powder with nano layer loaded on surface as well as preparation method and application of silver powder

    CN116117135A

  • Nanometer silver powder for conductive paste and preparation process and application of nanometer silver powder

    CN116329540A

  • High-tap-density high-dispersity nano spherical silver powder and preparation method thereof

    CN117680695A

Cited By

  • Preparation method of nano silver powder for pressure-sensitive thermistor and electronic paste of nano silver powder

    CN119819939A